Penyakit Gelisah (Anxiety/Al-Halu’) dalam Masyarakat Islam dDan Penyelesaiannya Menurut Psiko-Spiritual Islam - Saari, Che Zarrina (Jurnal Usuluddin, 2001)
This article tries to analyze the symptoms of anxiety disorder in modern psychology compared to the Islamic concept of al-Halu’. It also attempts to highlight the causes of anxiety in the Islamic society. Finally the article will try to suggest the methods of remedy of al-Halu’.